Propuesta para la reducción de carga contaminante en la empresa Productos El Tomatico S.A.S. en la zona dos de la empresa de alcantarillado y acueducto de Bogotá (2018)
The present graduation project is a proposal for the reduction of pollutant load of the residual water generated in the production process of the company Productos EL TOMATICO S.A.S., which is in charge of the design, production and commercialization of sauces and food preserves. Initially, a diagnosis was made of the processes carried out for the treatment and future discharge of the effluent from the company's production process, also a water balance in order to know the amount and proportion of water discharged from the process. The annual characterizations made by the company of the last two years (required by decree 3930 of 2010) were presented, evaluating the parameters that are outside the ranges established by resolution 0631 of 2015, which are COD, BOD5, and oils and fats. Three design alternatives were proposed for a new wastewater treatment, which met the necessary requirements to reduce the organic load present in the water. When an alternative was selected, the experimental development was carried out, evaluating the results with a new characterization to demonstrate the removal of the contaminant load present in the water. Based on the results, the design technical specifications were established, which depended on the results obtained in the laboratory, adapting them to industrial and commercial levels. Finally, the cost estimate of the selected alternative was calculated, taking into account the investment cost, which covers the capital expenditures (CAPEX), and the operating expenses (OPEX).